The Relationship Between Treatment Satisfaction and Medication Understanding Among Patients Taking a Novel Oral Pain Reliever: A Questionnaire-Based Cross-Sectional Study - Makio Takahashi; Sho Kodama; Maiko Akahane; Shuhei Yamamoto; Takashi Yonemoto; Haruhiko Seki (Pain and Therapy)
Abstract Introduction Patient satisfaction is important in pain management. Satisfaction with prescribed pain relievers and continued use of these drugs may be affected by a patient’s understanding of their efficacy and safety. We investigated the association between patients’ satisfaction and understanding of their prescribed medication for three oral pain relievers (lasmiditan, mirogabalin, and tramadol) that recently became available in Japan. Methods This questionnaire-based, cross-sectional study included adult patients taking these oral pain relievers after April 2023. The primary endpoint was overall satisfaction (five-point rating) and the secondary endpoint was overall understanding (five-point rating) of the oral pain relievers. Results In total, 328 patients (lasmiditan, 36.9%; mirogabalin, 55.5%, tramadol, 8.8%; four patients had been prescribed more than one medication) were included, and 71.6% of patients reported high satisfaction (score 4, 5) with their oral pain relievers (lasmiditan, 62.0%; mirogabalin, 76.1%; tramadol, 85.2%). The proportion of patients in the total population who reported a high understanding (score 4, 5) of their oral pain relievers was 68.0% (lasmiditan, 77.7%; mirogabalin, 63.3%; tramadol, 55.6%). In the total population and the lasmiditan and mirogabalin subgroups, the patient satisfaction level was significantly associated with scores on medication understanding (Cochran–Armitage test, p < 0.0001 for all). Discontinuation rates were higher in patients who were unsatisfied with their treatment than those who were satisfied (38.7% and 9.8%, respectively). Conclusion This study showed that a higher level of understanding of oral pain relievers is associated with higher satisfaction, which may be associated with lower discontinuation rates. Clinical Trial Registration UMIN000052629.